Vibration effect on ball score test in international vs. national level table tennis - Ardigò, Luca P.; Iacono, Antonio Dello; Zagatto, Alessandro M. [UNESP]; Bragazzi, Nicola L.; Kuvacic, Goran; Bellafiore, Marianna; Padulo, Johnny (Termedia Sp. z.o.o., 2018)
In table tennis, motor skills are crucial for discriminating player level. However, there is a dearth of studies exploring the impact of a vibrational stimulus on performance. Thirty-four male players (age 25×2 years; body mass index, BMI 23.4±1.2 kg·m-2) participated in the study. Seventeen played at international level (IL), while the remaining 17 played at national level (NL). The participants underwent a ball-handling test, the ball score, before (PRE) and after (POST) a vibrational stimulus. Intra-class correlation (ICC) for the ball score result showed good reliability (ICC 0.87 for IL and 0.80 for NL). Repeated measures ANOVA showed differences between groups for ball score (p=0.000) and a significant group × time interaction (p=0.004). Better performances were observed for the IL group than for the NL group, significantly only for POST. Vibration produced positive and negative effects in IL and NL groups, respectively.
Keywords: Fatigued conditions; Motor control; Muscle activity; Reaction time